Analisis Kerusakan Jalan menggunakan Metode Asphalt Institute - Eduardus Wunga Junior; Laurentio W. H. Leba; Sri Santi L. M. F. Seran (Local Engineering, 2023)
Pavement is a hard layer of skin (surface) that is placed on a soil formation after the completion of earthworks, or it can also be defined as a structure that separates the wheels of the vehicle from the subgrade. Road damage is a condition where the structural and functional roads are no longer able to provide optimal service to the traffic that crosses the road. Claret road, which is located in East Penfui Village, Kupang Regency, is the main route that connects several hamlets in East Penfui Village, namely hamlets 3, 4 and 5. Within these hamlets there are densely packed housing. Damage is starting to appear on this road from Sta 0–Sta 800. Visible damage includes longitudinal cracks, crocodile skin cracks, curling, loose grains, holes, poor drainage, and low quality of driving comfort. Using the asphal institute method, an average condition value of 54.86 was obtained, requiring additional types of patch and layer handling.